Counseling Employee Assistance Program (EAP) – SUPPORT To Improve Employee Mental Health at PT X Palembang - Hurriyati, Dwi; Ramadan, Rahmat (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
This community service activity aims to increase employee and community knowledge about the importance of the Employee Assistance Program (EAP) for employees designed by the company to improve employee mental health productivity. This service program is expected to help employees to prevent, identify and resolve employee problems, especially mental health, which impacts employee performance. This service activity is carried out at PT. X Palembang. The method of implementing community service activities is carried out to solve problems that exist among employees of PT. X Palembang related to mental health problems in the form of counseling efforts on the application and use of EAP program services at PT. X Palembang. The results of this community service activity are in the form of companion services for employees of PT. X Palembang to conduct coaching and counseling sessions to help solve employee problems to improve employee mental health.